2018
DOI: 10.3324/haematol.2018.195867
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical human models and emerging therapeutics for advanced systemic mastocytosis

Abstract: Mastocytosis is a term used to denote a group of rare diseases characterized by an abnormal accumulation of neoplastic mast cells in various tissues and organs. In most patients with systemic mastocytosis, the neoplastic cells carry activating mutations in KIT. Progress in mastocytosis research has long been hindered by the lack of suitable in vitro models, such as permanent human mast cell lines. In fact, only a few human mast cell lines are available to date: HMC-1, LAD1/2, LUVA, ROSA and MCPV-1. The HMC-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 110 publications
(176 reference statements)
0
21
0
Order By: Relevance
“…2 It is also pertinent to discuss the effect of IL-33 on nonallergic stimuli. We also showed that IL-33 augments the effect of the proinflammatory peptide substance P (SP) in stimulating secretion of impressive amounts of vascular endothelial growth factor (VEGF) 3 and TNF, 4 without concomitant secretion of tryptase, from human mast cells. The 1000-fold increase in secretion of TNF stimulated by IL-33 administered together with SP involves some interaction between their respective receptors.…”
Section: To the Editormentioning
confidence: 92%
See 1 more Smart Citation
“…2 It is also pertinent to discuss the effect of IL-33 on nonallergic stimuli. We also showed that IL-33 augments the effect of the proinflammatory peptide substance P (SP) in stimulating secretion of impressive amounts of vascular endothelial growth factor (VEGF) 3 and TNF, 4 without concomitant secretion of tryptase, from human mast cells. The 1000-fold increase in secretion of TNF stimulated by IL-33 administered together with SP involves some interaction between their respective receptors.…”
Section: To the Editormentioning
confidence: 92%
“…The understanding of mast cell biology has lagged somewhat behind studies on other effector cells because mast cells do not normally occur in blood, there is no human condition characterized by the absence of mast cells in all tissues, and there is no pharmacologic therapy that specifically and only silences mast cell function. However, the relatively recent availability of human mast cell lines, including LAD2 cells developed in our laboratory, 3,4 along with improved techniques to more easily culture human mast cells 5 and to more easily obtain mast cells from human tissues such as skin and marrow, 6,7 have facilitated research into this interesting cell.…”
Section: To the Editormentioning
confidence: 99%
“…A number of new drugs have been studied in recent years in in vitro experiments with mutated and wild-type KIT cellular lines [34]. Following the identification of CD30 expression on the surface of the neoplastic mast cell in vitro and among some patients with SM, the role of brentuximab-vedotin was evaluated.…”
Section: New Drugsmentioning
confidence: 99%
“…Mastocytosis is strongly linked to somatic mutations in the KIT gene (and especially the KIT D816V mutation) coding for the tyrosine kinase receptor KIT, which lead to constitutive activation 5 . However, it is now accepted that the KIT D816V mutation does not fully explain the spectrum of mastocytosis diseases.…”
Section: Introductionmentioning
confidence: 99%